Large‐Area (Ag, Cu)(In, Ga)Se2 Thin‐Film Solar Cells with Increased Bandgap and Reduced Voltage Losses Realized with Bulk Defect Reduction and Front‐Grading of the Absorber Bandgap. Issue 8 (6th May 2022) - Bothwell, Alexandra M.; Li, Siming; Farshchi, Rouin; Miller, Michael F.; Wands, Jake; Perkins, Craig L.; Rockett, Angus; Arehart, Aaron R.; Kuciauskas, Darius
Abstract : The 1.24 eV bandgap, 18.8% power conversion efficiency Ag‐alloyed chalcopyrite (Ag, Cu)(In, Ga)Se2 (ACIGS) solar cells are characterized to relate voltage and efficiency improvements to electro‐optical (EO) characteristics. Shockley–Read–Hall recombination center defect density, identified and characterized through deep level transient spectroscopy and time‐resolved photoluminescence (TRPL), is reduced through potassium and copper treatment optimization. Concomitantly, longer minority carrier lifetimes are achieved, which increases open‐circuit voltage ( V OC ). Near‐conduction band defects associated in earlier studies with light‐induced current instability are also mitigated. Analysis of charge‐carrier dynamics after single‐ and two‐photon excitation is used to separate recombination at the front interface and in the absorber bulk. From TRPL decay simulations, the authors estimate ranges of key solar cell material characteristics: bulk carrier lifetime τ bulk = 110–210 ns, charge‐carrier mobility μ = 110–160 cm 2 V −1 s −1, and front interface recombination velocity S front = 700–1050 cm s −1 . This lowest‐reported S front for ACIGS absorbers originates from the notched conduction band grading, which also makes the impact of the back interface recombination negligible. It is suggested in the results that solar cell performance enhancements can be made most readily with two distinct strategies: improving device architecture and reducing semiconductor defect densities. Using these approaches, power conversion efficiency in large‐area solar cells is improved by 1.1% absolute. Abstract : High‐efficiency, wide bandgap industrial (Ag, Cu)(In, Ga)Se2 solar cells are investigated to determine the device properties most significant to mitigating voltage losses. Through defect and device characterization of 18.8% efficient (Ag, Cu)(In, Ga)Se2 photovoltaic devices, two distinct strategies for voltage loss mitigation and more efficient solar cells compared to previously published work are demonstrated: reducing semiconductor defect densities and improving device architecture.